Informal settlements and the care of children 0–3 years of age: a qualitative study - Jegathesan, Thivia; Yousafzai, Aisha; Mantel, Michaela; Sereni, Vittorio; Armstrong, Robert W.; Minhas, Ripudaman Singh (Frontiers in Public Health, 2023)
Background: There is a rapid increase in urbanization with a high percentage of people living in poverty in urban informal settlements. These families, including single parents, are requiring accessible and affordable childcare. In Mlolongo, an informal settlement in Nairobi metropolitan area, Kenya, childcare centres, referred to as ‘babycares’, provided by local community members in the poor neighborhood environment are mushrooming without any standards or quality control. The objective of this study was to understand the current standard of babycare centres in informal settlements in Kenya through the perceptions of the local key stakeholders. Methods: Using a community based participatory approach, a qualitative study including focus groups with parents, community leaders and babycare centre employees/owners (referred to as caregivers) was conducted in the informal settlements of Mlolongo, Machakos County, Kenya. Results: Overall, community elders, parents and babycare centre caregivers feel that the centres are not providing an appropriate standard of care. The reported issues include lack of training and resources for caregivers, miscommunication between parents and caregivers on expectations and inappropriate child to caregiver ratio. Conclusion: The identified deficiencies and the potential for affordable quality childcare to support healthy child development in at-risk populations suggests that efforts need to be invested in defining effective models of care, such as social franchising, that can integrate within the community while at the same time meeting quality standards.